Study on the stability of HIV and syphilis reference materials under varied temperature conditions during their transportation - Márcia J. Castejon; Rosemeire Yamashiro; Camila C. Oliveira; Elaine L. Oliveira; Edilene P. R. Silveira; Carmem Aparecida F. Oliveira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: The objective of this study was to evaluate the short-term stability of the serum samples used as internal quality control (IQC) of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (Aids) and syphilis immunodiagnostic assays. These samples were produced at the Center of Immunology-Instituto Adolfo Lutz (IAL), and they were distributed to laboratories participating in the IAL Quality Control Program. Method: The sera analyzed by chemiluminescence assay were stored at varied temperature conditions: from 2ºC to 8ºC (refrigerator), from 15ºC to 25ºC (room temperature), at 37ºC (incubator) and at -20ºC (reference temperature) for 12 and 24 hours. Results: Comparative analysis of IQC results for anti-HIV and anti-T. pallidum (anti-treponemal) showed stability in the reference temperature and at the various simulated temperatures for transporting the samples at the established lengths of time. The data from the simple linear regression analysis of negative serum samples (incubator/24 hours) and in one batch of HIV IQC (room temperature/24 hours) were statistically significant at the level of 5% (p-value < 0.05). Conclusion: The sera presented necessary requirements as reference material to be transported to laboratories at refrigeration temperature (2ºC to 8ºC), at the maximum shipping time of 12 hours.